Docking and Molecular Dynamic Simulations Study to Search Curcumin Analogue Compounds as Potential Inhibitor Against SARS-CoV-2: A Computational Approach - Veza Azteria; Neni Frimayanti; Adel Zamri; Yum Eryanti; Noval Herfindo (Jurnal Kimia Sains dan Aplikasi, 2021)
Coronavirus is a pandemic in the world. It requires researchers and scientists to work hard to find a vaccine or drug to inhibit the development of the coronavirus. Many drugs have been used, such as remdesivir, lopinavir, and chloroquine. However, how effective is the use of these drugs for inhibiting the coronavirus’s growth? There is no research has been done. Curcumin is now known as one of the compounds that have some biological activities, and it is also can potentially be used as a CoV-2 inhibitor. The computational study, i.e., molecular docking and molecular dynamic, can help researchers to predict which compounds have the potential as an inhibitor against the CoV-2 coronavirus. In this study, lopinavir was used as a positive control. Lopinavir and 45 curcumin analog compounds were docked against the main protease protein with 6LU7 PDB ID. Based on the docking results, it was discovered that compound 1, compound 2, and compound 4 have the same binding orientation as lopinavir. Molecular dynamic simulation with the lowest binding free energy conformation was used to check these compounds’ stability. Only compound 4 was maintained to observe hydrogen bonding with Lys5 and Lys137 with a distance of 2.9 Å. The distance of hydrogen bonds and binding free energy over simulation time is essential to elucidate the potential compound’s affinity. For then, compound 4 can be used as a potential inhibitor against the CoV-2 coronavirus.